Tracing Morphophonemic Change in Qur'anic Arabic: I'lal in the Verbal System of Surah Hud - Dzikri Cahya Mahesa; Fathir Khalid; Muhammad Nurhasan; D Dayudin; A Akmaliyah (QiST: Journal of Quran and Tafseer Studies, 2026)
Purpose - This study aims to investigate the morphophonemic process of i'lal in Arabic verbs (fi'il) containing weak letters (ḥurūf al-'illat) in Surah Hud. The research was conducted to explain how phonological changes in Qur'anic Arabic operate systematically according to the principles of ṣaraf and to demonstrate their linguistic relevance in maintaining phonetic ease and morphological balance. The study argues that the phenomenon of i'lal in Surah Hud reflects a structured interaction between morphology and phonology in classical Arabic.Design/methods/approach - This research employs a qualitative descriptive method within the framework of Arabic morphophonemics and ṣaraf theory. The data consist of Qur'anic verbs in Surah Hud that undergo phonological changes involving weak letters. Data collection was carried out through intensive reading, documentation, and classification of relevant verbs. The analysis focused on identifying the original forms of the verbs, tracing phonological transformations, and categorizing the types of i'lal.Findings - The study identifies five major types of i'lal in Surah Hud: i'lal bil ḥadzfi, i'lal bit taskīn, i'lal bin naqli, i'lal bil qalbi, and i'lal bil ibdal. These changes occur consistently according to Arabic morphological rules and primarily function to facilitate pronunciation efficiency while preserving the grammatical structure of Qur'anic Arabic. Among these types, i'lal bil qalbi and i'lal bil ḥadzfi appear most frequently in the analyzed data.Research implications/limitations - This study is limited to verbs found in Surah Hud and focuses specifically on morphophonemic aspects of i'lal. Therefore, the findings cannot be generalized to all Qur'anic surahs or broader Arabic linguistic structures without further comparative studies. Future research may expand the corpus to other surahs or explore syntactic and semantic dimensions of i'lal.Originality/value - This study contributes to Arabic linguistic scholarship by providing a systematic morphophonemic analysis of i'lal in Qur'anic fi'il. It offers a detailed classification of phonological transformations in Surah Hud and strengthens the integration of ṣaraf theory with modern morphophonemic approaches in Qur'anic studies.